2016
DOI: 10.7860/jcdr/2016/21925.8718
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Ectopic Pregnancies in a Tertiary Care Centre in Southern India: A Six-Year Retrospective Study

Abstract: IntrOductIOnEctopic Pregnancy (EP) is a pregnancy implanted outside the cavity of the uterus. It is well recognised as a life-threatening emergency in early pregnancy. The incidence of EP is around 1-2% in most hospital based studies [1][2][3][4][5][6].Diagnosis requires a high index of suspicion as the classic triad of amenorrhoea, abdominal pain and vaginal bleeding is not seen in majority of cases. Women may present with non-specific symptoms, unaware of an ongoing pregnancy or even present with haemodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
73
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(105 citation statements)
references
References 13 publications
15
73
2
Order By: Relevance
“…21 In Tahmina et al 15.3% and Porwal S et al it is 15.3% and 47.5% respectively. 15,16 In present study H/O infertility was found in 16.1% which is comparable to other studies like 12.9% in Tuli AG et al study. 19 In present study 4% cases had previous H/O previous ectopic pregnancy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…21 In Tahmina et al 15.3% and Porwal S et al it is 15.3% and 47.5% respectively. 15,16 In present study H/O infertility was found in 16.1% which is comparable to other studies like 12.9% in Tuli AG et al study. 19 In present study 4% cases had previous H/O previous ectopic pregnancy.…”
Section: Discussionsupporting
confidence: 88%
“…15 The incidence of EP was 0.91% in a study by tahmina. 16 The increase in incidence is associated with rise in the incidence of sexually transmitted infections (STIs) and salpingitis, advances in assisted reproductive technology, tubal surgeries, female contraception and earlier diagnosis with more sensitive methods.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] The peak age of incidence in this study is 20-25 years (33.84%) which is consistent with the study of Gupta et al (47.5%) and Karmakar et al (44%). 8,9 In this study ectopic pregnancies were found to be present more commonly in third gravidae (46.3%) followed by second gravidae (24.5%) and fourth or more gravidae (18.3%).…”
Section: Discussionsupporting
confidence: 82%
“…Mean gestational age at diagnosis of EP was 7.1 in the study conducted by Tahmina S et al while Khaleeque et al, reported 6 weeks at diagnosis. 24,25 The classical triad of amenorrhoea, pain and vaginal bleeding was seen in 28.57% patients in present study, as compared to Tahima S et al, wherein, this triad was seen in 40.3% cases. Other studies have reported this triad to be present in 28-95% women, clearly indicating that this is not a presenting feature in most cases.…”
Section: Discussionsupporting
confidence: 42%